Copy that: an analysis of homogeneity at News24 and IOL - Kassiem, A’Eysha (Stellenbosch : Stellenbosch University, 2025)
ENGLISH ABSTRACT: This study investigates the homogeneity between two of South Africa’s biggest online platforms – News24 and iol. At its dawn, online news platforms were heralded as a boon for democracy due to its interactivity. A multitude of news platforms would result in a wide variety of stories and diverse voices. However, the demands of an always-on platform, the constant pressure of immediacy and increased competition often result in homogeneous content. The theoretical underpinning of this study is Habermas’s public sphere theory, which is centred on the role of public participation and citizen-to-citizen engagement within a democracy. The normative notion is that news informs the public. Therefore, the way news stories are structured and what information is presented is critical to the way the public is informed. Using a qualitative approach, this study employs a content comparison to analyse stories that cover the same topic or event during the week of the State of the Nation Address in 2022, up to and including President Cyril Ramaphosa’s address. The content analysis is done specifically in terms of angle, sources, structure and narrative. This study also aims to highlight in what way homogeneous stories differ. As the findings show, while online news between News24 and iol are homogeneous in subject matter, the information contained in the sampled articles is stark. This means that although these two sites do not carry replica content, the information contained in articles that cover the same topic or event are so factually different that citizens would not be able to rationally engage. This disparity in information therefore has a bearing on the quality of the conversation between citizens and, in turn, public participation in a democracy.